Evaluation procedure for economic efficiency of occupational injuries preventive measures with risk-based approach - Evtushenko, Olga; Siryk, Alina; Porodko, Petro (My University, 2017)
Proposed methodology on the classic approach to economic calculations and “risk price” indicators, a procedure for determining the economic effectiveness of occupational injuries preventive measures was designed.
Keywords: кафедра екології та екоменеджменту; occupational injuries; risk; economic calculations; виробничий травматизм; ризик; економічна ефективність; производственный травматизм; риск; экономическая эффективность